2012
DOI: 10.1177/0095798412461808
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Prolonged Activation and Anticipatory Race-Related Stress Scale

Abstract: This article describes two separate studies that were conducted to develop and validate a measure of the prolonged stress activation and anticipatory race-related stress response in African American adults (Prolonged Activation and Anticipatory Race-Related Stress Scale [PARS]). In Study 1, an exploratory factor analytic procedure (N = 292) resulted in a 17-item measure with four underlying factors: (a) Perseverative Cognition, (b) Secondary Appraisal, (c) Anticipatory Race-Related Stress Scale-Psychological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 47 publications
(78 reference statements)
1
101
0
Order By: Relevance
“…However, the inclusion of family and friends provides further information on perceptions of racial discrimination among those within their familial and social networks. Research also has indicated that individuals can be impacted by racial discrimination experienced by people close to them in their social network (28). Others have reported that perceived healthcare-specific racial discrimination may have a role in the development of cultural mistrust of the provider and the medical system, as well as the appropriateness of care provided to patients, which reflects an area of concern for Black MSM (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the inclusion of family and friends provides further information on perceptions of racial discrimination among those within their familial and social networks. Research also has indicated that individuals can be impacted by racial discrimination experienced by people close to them in their social network (28). Others have reported that perceived healthcare-specific racial discrimination may have a role in the development of cultural mistrust of the provider and the medical system, as well as the appropriateness of care provided to patients, which reflects an area of concern for Black MSM (24).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, chronic discrimination has been shown to have even more wide‐ranging effects on the mental and physical health of Black adults (Ong, Fuller‐Rowell, & Burrow, 2009). For example, Black adults who report exposure to chronic discrimination are more likely to report higher numbers of stressful life events (Harrell, 2000; Ong et al, 2009), to engage in maladaptive coping behaviors (Martin, Tuch, & Roman, 2003), and to have higher rates of hypertension, cardiovascular disease, and diabetes (Utsey, Belvet, Hubbard, et al, 2013). Given the robust associations between discrimination and physical and psychological distress, an examination of whether perceived discrimination can serve as a specific painful and provocative event that contributes to capability for suicide is warranted.…”
Section: Discrimination As a Painful And Provocative Eventmentioning
confidence: 99%
“…While scholars note that these responses, governed largely by the sympathetic nervous system, may continue long after a racially discriminatory event occurs (Dorr et al, 2007; Harrell, 2000; Utsey et al, 2013), few studies examine the longer-term effects of racial discrimination (see Hoggard et al, 2015, for an exception). For instance, Dorr et al, 2007 found that AAs who inhibited their anger following a racist or nonracist debate with a European American (EA) confederate experienced delayed total peripheral resistance recovery during a 10-minute recording period.…”
Section: Introductionmentioning
confidence: 99%